Achieving exceptional radiation tolerance with crystalline-amorphous nanocrystalline structures. (March 2020) - Jin, Miaomiao; Cao, Penghui; Short, Michael P.
Graphical abstract: Abstract: Nanostructured materials with amorphous intergranular films (AIFs) have demonstrated superior strength and ductility. Their radiation tolerance is expected to be high as the large fraction of interfacial volume efficiently sinks radiation-induced defects. Here we demonstrate how a crystalline-amorphous system (nanocrystalline Cu with Zr-doped AIFs) responds to continuous irradiation with molecular dynamics simulations. We propose a diffusion model that well characterizes the cascade-driven mixing process, and reveal that the spread of Zr distribution scales linearly with the damage level. The exceptional radiation resistance is attributed to the interfaces acting as sustainable defect sinks, Zr mixing into the bulk to enhance local defect annihilation due to solute-interstitial dragging, and Zr impeding radiation-enhanced grain growth by restraining AIFs from migration and maintaining interface stiffness. These findings suggest that AIF-engineered systems hold promise as highly radiation-tolerant materials with strong structural stability and self-healing capability under radiation damage.